Seeking Alpha: Excess Risk Taking and Competition for Managerial Talent - Acharya, Viral; Pagano, Marco; Volpin, Paolo (Review of Financial Studies, 2016)
We present a model in which firms compete for scarce managerial talent ("alpha") and managers are risk averse. When managers cannot move across firms after being hired, employers learn about their talent, efficiently allocate them to projects, and provide insurance to low-quality managers. When, instead, managers can move across firms, firmlevel coinsurance is no longer feasible, but managers may self-insure by switching employer to delay the revelation of their true quality. However, this results in inefficient project assignment, with low-quality managers handling projects that are too risky for them.